Abiotic Stresses, Biostimulants and Plant Activity - Del Buono, Daniele; Proietti, Primo; Regni, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Numerous biotic and abiotic stresses can significantly decrease crop growth and yields. In the context of climate change, stresses will be more frequent in the coming years and will have an even more severe impact on agricultural systems. As a result, crop production could be drastically reduced, with the consequences aggravated by the fact that the world's growing population will require more food production. Furthermore, among abiotic stresses, the salinity of soils and water for agricultural use, as well as drought, particularly impact crops. For these reasons, sustainable measures need to be implemented to maintain/increase crop production and ensure the resilience of agricultural systems. To this end, biostimulants, materials that can increase crop productivity and the quality profile of end products, are an increasingly popular solution. The primary function of biostimulants is improving nutrient use efficiency, quality traits, and stress tolerance, as well as ensuring the bioavailability of nutrients in the soil or rhizosphere. Therefore, this Special Issue published research on the effects of biostimulants on helping crops to cope with abiotic stresses, focusing on salt and drought stress. In addition, scientific contributions on the use of biostimulants to counteract other abiotic stresses, such as potentially toxic metals and extreme temperatures, are also welcome. New substances with biostimulant action and studies investigating the mechanisms of action of biostimulants and their qualitative, economic, and environmental benefits will also be considered.